Molecular and Cellular Mechanisms Driving Cardiovascular Disease in Hutchinson-Gilford Progeria Syndrome: Lessons Learned from Animal Models - Ignacio Benedicto; Beatriz Dorado; Vicente Andrés (Cells, 2021)
Hutchinson-Gilford progeria syndrome (HGPS) is a rare genetic disease that recapitulates many symptoms of physiological aging and precipitates death. Patients develop severe vascular alterations, mainly massive vascular smooth muscle cell loss, vessel stiffening, calcification, fibrosis, and generalized atherosclerosis, as well as electrical, structural, and functional anomalies in the heart. As a result, most HGPS patients die of myocardial infarction, heart failure, or stroke typically during the first or second decade of life. No cure exists for HGPS, and therefore it is of the utmost importance to define the mechanisms that control disease progression in order to develop new treatments to improve the life quality of patients and extend their lifespan. Since the discovery of the HGPS-causing mutation, several animal models have been generated to study multiple aspects of the syndrome and to analyze the contribution of different cell types to the acquisition of the HGPS-associated cardiovascular phenotype. This review discusses current knowledge about cardiovascular features in HGPS patients and animal models and the molecular and cellular mechanisms through which progerin causes cardiovascular disease.